Threats to water security - McCartney, Matthew P. (2020)
Socio-economic development and availability of water are strongly interrelated. Advances in water related engineering, technology and management have been central to progress in human development. Today water remains central to many aspects of socio-economic development – key to energy and food production (nexus) and other areas of human endeavor.